METHODOLOGICAL AND APPLIED PRINCIPLES OF ANTI-CRISIS MANAGEMENT AT AN ENTERPRISE: ASPECTS OF ADAPTATION IN THE SECURITY SPHERE - BILETSKA, Iryna; IABLON, Volodymyr (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The study focuses on the issue of anti-crisis management of business entities with a view to ensuring adaptation and forming an appropriate level of economic security of business in turbulent conditions. The aim of the research is to further develop the methodological and applied principles of anti-crisis management at the enterprise in the context of ensuring the adaptation of its activities and development to the principles of economic security of the business. It is proved that in the environment of significant socio-economic transformations, increased external threats, martial law and the growth of internal risks for business, the problem of ensuring effective anti-crisis management is becoming key. The factors and problems of the environment that actualize the issue of anti-crisis management and adaptation of business entities are identified. The need for the development of scientifically sound methodological and applied principles of anti-crisis management in order to preserve the functional viability of enterprises is substantiated. The interrelationships between anti-crisis management and ensuring the economic and corporate security of enterprises are shown, which covers not only financial stability, but also protection against cyber threats, information leaks, unfair competition, internal abuses and the destruction of institutional trust. The vectors of formation and implementation of management mechanisms for conditions of increased uncertainty as part of standard crisis response tools are indicated, and the systemic integration of risk and security management elements into the overall management structure. The paper outlines the security and adaptation risks of enterprises associated with military operations, infrastructure destruction, and energy instability and the need to maintain competitiveness. The directions for the formation of universal and at the same time flexible management models that are able to adapt to different scenarios of events and at the same time ensure the systemic stability of enterprises in the field of security have been identified.
Keywords: enterprise management; economic security; sustainability; viability; business adaptation; anti-crisis management; stability; development; management